Rekayasa Ulang Dongkrak Rel Kereta Api Kapasitas 10 Ton - Surasno Surasno; Budi Tjahjohartoto (Center for Material and Technical Product, 2014)
Mechanical rail jack with capacity of 10 tons and high leverage of 50-10 cm which is used by PT. KAI have a relatively short lifetime and easily damaged. On the damage rail jack or that does not function has been done failure analysis, which showed that the rails jack damaged or malfunction caused by a broken (chipped) on the lifting gear rack that corrosion initiated at inside parts of the frame, bushing, gear rack lifter, pinion shaft, and the main spline. This component becomes thin, the contact area on the teeth become loose and receive dynamic cyclic load then fracture occurs. To improve the quality of rail jack, reengineering was done by replacing the material specifications of components, especially components that have contact areas such as lifting gear rack, gear, pinion shaft, the main spline, bushing and pedestal. Steel metal materials for the components of the rail jack were selected from tool steel AISI 4043 (DIN 1.6511-34NiCrMo6), DIN 1.2510 (100MnCrW4) and common carbon steel (St. 37 and St. 42) with appropriate heat treatment. Furthermore, modification was made on lifting angle of gear-rack from 5 degree to 20 degree. The the pressure test on 5 and 10 ton loads show good results, no changes in shape and meet the technical requirements of the PT. KAI. Dongkrak rel mekanik daya angkat 10 ton dan tinggi ungkit 5–10 cm yang digunakan oleh PT. KAI life time-nya relatif pendek dan cepat rusak. Dari failure analysis yang telah dilakukan terhadap dongkrak yang rusak,menunjukkan bahwa rusak atau tidak berfungsinya dongkrak rel disebabkan oleh patah (gompal) pada gigi rack pengangkat yang diawali korosi pada rangka bagian dalam, bushing, gigi rack pengangkat, poros pinion, dan spline utama. Komponen ini menipis, bidang kontak gigi menjadi longgar dan menerima beban dinamik siklik sehingga terjadilah patah. Untuk meningkatkan kualitas dongkrak rel telah dilakukan rekayasa ulang dengan mengganti spesifikasi bahan komponen terutama komponen yang mempunyai bidang kontak seperti gigi rack pengangkat, roda gigi, poros pinion, spline utama, bushing dan tumpuan. Bahan logam baja untuk komponen dongkrak rel dipilih dari baja perkakas AISI 4043 (DIN 1.6511-34NiCrMo6), DIN 1.2510 (100MnCrW4) dan baja karbon umum (St. 37 dan St. 42) dengan heat treatment yang tepat. Selanjutnya melakukan modifikasi desain sudut gigi rack pengangkat dari 5 derajat menjadi 20 derajat. Hasil uji tekan beban 5 dan 10 ton menunjukkan hasil yang baik, tidak terjadi perubahan bentuk dan memenuhi persyaratan teknis PT. KAI.